Role of Intravenous Levetiracetam in Acute Seizure Management - Batool F. Kirmani (Frontiers Research Topics, 2014)
Intractable epilepsy still remains the main issue despite new advances in medical and surgical treatment of epilepsy. Acute seizure management in a timely manner is crucial to prevent irreversible brain damage. Benzodiazepines still remain the first initial treatment to abort the seizure activity. The approval phenytoin, fosphenytoin, intravenous valproate, and rectal diazepam provided additional options. The approval of intravenous levetiracetam gave another option to physicians if and when the above treatment fails to control the seizure activity. In this Ebook, we have included chapters from renowned researchers in the field of neurology and epilepsy who have covered the various aspects of these agents in detail including the properties, mechanism of action, pharmacology, neurobehavioral effects, and the roles of these agents in special populations including traumatic brain injury and brain tumor related epilepsy. These data further show that intravenous levetiracetam can be used in acute seizure management and in special circumstances.